(3eHGOF GdGbJUGO GdSjGSj (B:s (3GdCSGSjGJ (B/s - (3OhjOGQ, eMeOs ((3GdLRGFQ(B: s (3GdeDSSI GdhWfjI ddafhf GdeWHYjI(B, s, 2004)
(3GdGbJUGO GdSjGSj Yde GLJeGYj, GdGbJUGO GdSjGSj cYde, JGQjN GdGbJUGO GdSjGSj, GdBbJUGO GdSjGSj Yde WQb GdGfJGL, GdGbJUGO GdSjGSj hGdQCSeGdjI, GdfXQjI Hj GdcdGSjc heGQcS, GdfXQj(Bd (3GdGbJUGOjI ddeOQSI GdfjhcdGSjcjI, a jfbO GdfXQjI GdMOjI aj JMOjO GdGKeGf, GdLhGfH GdSdHjI ddYedjI GdGbJUGOjI GdQCSeGdjI, GdGbJUGO GdSjGSj hGdGTJQGcjI, GdJQcjH GdJfXjej ddGbJUGO GdeNWW, YedjI GdJNWjW GdGbJUGOj, GdeTcdGJ GdGbJUGOjI ceG JYQV aj GdGbJUGO GdeNWWs
(3GdeQGLY U(B.1059((3GbJfGAGJ (B2014 01(3f(B) (3L(B1-(3GdCSGSjGJ L(B2-(3GdGbJUGO GdfbOj L(B3-(3GdGbJUGO GdOhdj L(B4-(3GdGbJUGO GdeGdjs